Content Marketing Strategy Through Instagram for Kepahiang Coffee MSME Based on SWOT Digital Framework - Faisal Dwi Putra; Tiza Tania; Sintia Safrianti; Veny Puspita; Janusi Waliamin (Penerbit Goodwood, 2025)
Purpose: The COVID-19 pandemic accelerated digital adoption among Indonesian Micro, Small, and Medium Enterprises (MSMEs), increasing the need and opportunity for Instagram marketing. This study develops a content strategy for Kepahiang Coffee MSMEs in Bengkulu to bridge product quality with limited online reach.Research Methodology: A qualitative descriptive design was used. Data were obtained from secondary sources (journals, APJII reports, government documents) and direct observation of Kepahiang Coffee MSMEs. SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis was used to assess internal and external conditions and develop content marketing strategies. Results: SWOT analysis shows Kepahiang Coffee MSME has strong product quality and organic sourcing but weak digital marketing. Market opportunities are high due to rising coffee consumption and diversification trends. The study proposes an Instagram content strategy: introduction (50%), branding (30%), and sales (20%).Conclusions: Instagram content marketing based on highland origin, organic production, and farmer narratives is a feasible and cost-effective strategy for Kepahiang Coffee MSME.Limitations: This study relies primarily on secondary data and SWOT analytical framework without empirical testing through implementation and consumer response measurement. Contributions: This study offers a replicable Instagram content marketing framework for Indonesian highland coffee MSMEs, using SWOT-based analysis for context-specific digital strategy design.